Zánĕtlivá reakce a její význam v průbĕhu nádorového procesu - Hlávková, D; Kopecký, O; Lukesová, S (Vnitrni lekarstvi, 2008)
This article gives basic information about the formation and the course of the inflammatory reaction, which is the important adaptation mechanism of the organism on the various external and internal injurants. The main attention is fixated on the role of the immune system in the course of the inflammatory reaction. It deals with the presence and the sense of the inflammatory reaction in the tumour environment in more detail. It gives the short information about the mechanisms of the antitumour defence. The influence ofthe inflammatory reaction on the genesis, the course and the progression of the tumour disease is discussed in the third chapter.
Keywords: zánět; chemokiny; nádory; Acute-Phase Reaction; Chemokines; Animals; lidé; Inflammation; Neoplasms; reakce akutní fáze; Humans; zvířata